ACCOUNTANTS AND AUDITORS' PERCEPTIONS OF TECHNOLOGY AND ATTITUDE OF INTEGRITY IN PREVENTING FRAUD - Fifitri Ali; Alex Handro (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Fraud can be interpreted as fraud which contains the meaning of irregularities and acts against the law, which are carried out intentionally for certain purposes. The role of accountants is often questioned when it comes to financial statement fraud. The audit expectation gap indicates that public expectations are not met for the role of accountants in all fraud cases. This study aims to see if there is a common perception between accountants and auditors in determining the most effective technology and integrity attitude in preventing fraud. Data collection was carried out by distributing a questionnaire link to 110 accounting alumni of the Riau Caltex Polytechnic who graduated from 2015 to 2019 and worked as accountants or auditors. Hypothesis testing is done by using independent sample t-test or different test t-test. The results showed that there were differences in perceptions between accountants and auditors in the selection of technology, namely protection against viruses and the installation of CCTV surveillance camera equipment. However, overall, the results showed no difference. Accountants and auditors have the same perception regarding the attitude of pure integrity which is chosen to be the most effective attitude of integrity to have in order to prevent fraud.